2013
DOI: 10.1002/cplu.201300123
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Oxidation of 9H‐Fluorenes to 9‐Fluorenones using Mono‐/Multilayer Graphene‐Supported Alkaline Catalyst

Abstract: The synthesis of 9‐fluorenone derivatives has been achieved in high yield and with high purity by aerobic oxidation of 9H‐fluorenes at room temperature in the presence of a graphene‐supported KOH composite that acts as a catalyst in N,N‐dimethylformamide. The new protocol involves very simple work‐up procedures, and the solvent and the catalyst can be recycled and reused. A scaled‐up preparative study employing this method was also conducted and showed its advantages of being both cost‐effective and environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 76 publications
1
17
0
Order By: Relevance
“…During this study they found that trialkoxy truxenes can be converted in sufficient yield into the truxenones with tetramethylammonium hydroxide and oxygen in THF. Recently, a mixture of KOH and graphene at room temperature in air was used to oxidize truxene to truxenone in 93 % yield . During our ongoing research on the conversion of truxenes into truxenones, we found an unprecedented oxidative dimerization reaction that connected two or three truxenes at benzylic fluorene positions through a highly strained double bond.…”
Section: Methodsmentioning
confidence: 99%
“…During this study they found that trialkoxy truxenes can be converted in sufficient yield into the truxenones with tetramethylammonium hydroxide and oxygen in THF. Recently, a mixture of KOH and graphene at room temperature in air was used to oxidize truxene to truxenone in 93 % yield . During our ongoing research on the conversion of truxenes into truxenones, we found an unprecedented oxidative dimerization reaction that connected two or three truxenes at benzylic fluorene positions through a highly strained double bond.…”
Section: Methodsmentioning
confidence: 99%
“…13,14 Recently, some attempts have been made to combine graphene with semiconductor photocatalysts to enhance the performance of the catalysts due to graphene's excellent electron transport capability and its ability to induce visible-light responsive activity. [15][16][17] Graphene oxide (GO) can be prepared in a two-step process: chemical oxidation of graphite followed by sonication.…”
Section: Introductionmentioning
confidence: 99%
“…Also, with the material size decreasing, the specific surface area and surface-to-volume ratio increase dramatically, leading to their remarkable properties and important application (Alivisatos, '96;Megelski et al, 2002;Chen et al, 2005;Chen and Mao, 2007;Wang et al, 2015). The physical properties of nanomaterials are closely related to their morphology and size (Murray et al, 2000;Chen and Mao, 2007;Zhang et al, 2013b;Stacy et al, 2014;Zhang and Weeks, 2014). To date, a variety of shapes with notable examples, including nanospheres Tu et al, 2014;Weng et al, 2014), nanowires Wang et al, 2003), nanofibers (Li et al, 2013), nanotubes (Eder, 2010;Nasibulin et al, 2011;Meng et al, 2014), nanosheets (Hosono et al, 2005;Wang et al, 2008;Huang et al, 2014), nanoporous (Jun et al, 2000;Zhang et al, 2013a;Kim and Choi, 2014;Qiu et al, 2014), and core-shell structures (Bao et al, 2004;Sun and Li, 2004), have been reported.…”
Section: Introductionmentioning
confidence: 99%